Saint Vincent and the Grenadines. Significant achievements 2022 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
The activities carried out by the Saint Vincent and the Grenadines Delegation of 2022 are identified, focus to needs and interests of the country such as; strengthened the capacity of farming families to improve their capacity to produce vegetables for the domestic market; promoted and supported knowledge to drive the development of the apiculture industry in the Caribbean; IICA conducted a baseline survey on the impact of COVID-19, climate change and recent volcanic eruptions on rural households; improved the capacity of primary schools to learne how to sustainably operate gardens as pedagogical tools to train students and teachers in vegetable production; primary producers, farmers and fisherfolk, were improved their capacity to produce high-quality products to supply the domestic market; and finally, maked training program to various stakeholders and hosted a trade fair to share new knowledge and foster business opportunities in the region.